Plasma levels of trimethylamine-N-oxide are confounded by impaired kidney function and poor metabolic control. Issue 2 (December 2015) - Mueller, Daniel M.; Allenspach, Martina; Othman, Alaa; Saely, Christoph H.; Muendlein, Axel; Vonbank, Alexander; Drexel, Heinz; von Eckardstein, Arnold
Abstract: Background: After ingestion of phosphatidylcholine, l -carnitine or betaine, trimethylamine-N-oxide (TMAO) is formed by gut microbiota and liver enzymes. Elevated TMAO plasma levels were associated with increased cardiovascular risk and other diseases. Also betaine and choline itself were recently associated with increased cardiovascular risk. Methods: A newly developed LC-HRMS method was applied to measure the plasma concentrations of TMAO, betaine and choline in a cohort of 339 patients undergoing coronary angiography for the evaluation of suspected coronary artery disease. Results: Betaine concentrations in males were significantly higher than in females (42.0 vs. 35.9 μmol/L; p < 0.001). Plasma concentrations of TMAO but not of betaine or choline were higher in patients with diabetes compared to euglycemic patients (2.39 vs. 0.980 μmol/L; p = 0.001) as well as in patients with metabolic syndrome as compared to patients without metabolic syndrome (2.37 vs. 1.43 μmol/L; p = 0.002). Plasma concentrations of TMAO or choline increased significantly with decreasing renal function (Spearman's rho: −0.281; p < 0.001). However, plasma levels of TMAO or betaine were associated with neither a history of myocardial infarction nor the angiographically assessed presence of coronary heart disease, nor incident cardiovascular events during 8 years of follow-up. Plasma levels of choline were significantly lower in patients with a history of acute myocardial infarction as compared to those without such history (10.0 vs. 10.8 μmol/L; p = 0.045). Conclusions: Plasma levels of TMAO are confounded by impaired kidney function and poor metabolic control but are not associated with the history, presence or incidence of symptoms or events of coronary heart disease. Highlights: We measured TMAO, betaine and choline in 339 patients. TMAO is confounded by impaired kidney function and poor metabolic control. TMAO is not associated with presence or incidence of coronary heart disease.